2004
DOI: 10.1038/modpathol.3800163
|View full text |Cite
|
Sign up to set email alerts
|

p63 expression in assessment of bronchioloalveolar proliferations of the lung

Abstract: Discrimination of well-differentiated pulmonary adenocarcinoma from reactive bronchioloalveolar epithelium can be difficult on routine histology, especially with small biopsies. Ancillary studies to help in this distinction are desirable. p63, a p53-homologous nuclear protein, is a marker of reserve cells of the bronchus and terminal lobular unit. In this study, 33 cases of adenocarcinoma (20 open lung and 13 transbronchial/percutaneous biopsies) and 43 cases of benign lungs with fibrosis and metaplasia (22 op… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
39
0

Year Published

2005
2005
2015
2015

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 56 publications
(43 citation statements)
references
References 16 publications
4
39
0
Order By: Relevance
“…This finding indicates that, although uncommon, p63 expression can occur in these tumors, but when present, the percentage of positive cells is usually lower than that seen in squamous carcinomas. It should also be mentioned that p63 has also been reported in 12-33% of the lung adenocarcinomas, 43,45,49 a finding which indicates that p63 immunostaining has no utility in distinguishing these tumors from mesotheliomas.…”
Section: Discussionmentioning
confidence: 99%
“…This finding indicates that, although uncommon, p63 expression can occur in these tumors, but when present, the percentage of positive cells is usually lower than that seen in squamous carcinomas. It should also be mentioned that p63 has also been reported in 12-33% of the lung adenocarcinomas, 43,45,49 a finding which indicates that p63 immunostaining has no utility in distinguishing these tumors from mesotheliomas.…”
Section: Discussionmentioning
confidence: 99%
“…BSCs also line this region of the airway tract in humans but their presence has not been well documented in rodent lungs (Chilosi et al, 2002;Sheikh et al, 2004). There is evidence that, in the bronchiolar region, a subpopulation of secretory cells that express Scgb1a1 but lack expression of Cyp2f2 can act as facultative progenitor cells.…”
Section: Cell Types Involved In the Regenerative Responsementioning
confidence: 99%
“…18 Upon damage in airway epithelium, the basal cells show increased reactivity demonstrated by increased expression of p63, a basal cell restricted transcription factor and its downstream target cytokeratin 14 (CK14). 19,20 Recent studies have implicated p63 with EMT. Das et al 21 showed that fibrotic lesions in oral submucosa showed marked upregulation of p63 and Oh et al 22 showed that primary human keratinocytes transfected with ΔNp63 underwent EMT when they had depleted their normal proliferative capacity.…”
mentioning
confidence: 99%